The ex-ante effects of non-contributory pensions in Colombia and Peru (2014)
The aim of this paper is to study the ex-ante e ects of the implementation of a Non Con- tributory Pension (NCP) program in Colombia and Peru. Relying on household survey data, we simulate the potential impact of the transfer on poverty, inequality, scal cost, and the probability of a liation to the contributory pension system. This last e ect is the most direct behavioral e ect one can expect from the implementation of a NCP scheme. For the behavioral response we estimate a Nested Logit Model. Our results show that a NCP in Colombia and Peru contributes to the reduction of poverty and inequality among the elderly, particularly in rural areas at a ordable scal costs. Furthermore, there is not a large impact on the prob- ability of a liation to contributory pensions when the program is targeted to the poor (and extreme poor), with the exception of Peruvian women for whom there is always a sizeable reduction on their probability of a liation to the contributory pension system.